Determination of Polycyclic Aromatic Hydrocarbons in Surface Water of Shatt Al-Hilla River - F. Karam, Faiq; H. Hussein, Falah; J. Baqir, Sadiq.; M. Abid, Fadhil (Asian Journal of Chemistry, 2012)
Polycyclic aromatic hydrocarbons were analyzed in surface water of Shatt Al-Hilla river (middle of Iraq). Surface water samples originated from 14 sites with a differentiated human influence starting from Sadat Al-Hindya to southern border of Hilla governorate. Polycyclic aromatic hydrocarbons were extracted simultaneously by solid phase extraction using syback-18 with dichloromethane as solvent and then analyzed by HPLC. The polycyclic aromatic hydrocarbons concentrations were ranged between (1.08-1177.20) ng.mL-1. The results showed the most pollutant sites was S7, which is represent the sewage pipe that came from Sooq Al-Hilla were contaminated with 12 compounds of polycyclic aromatic hydrocarbons. Fifteen polycyclic aromatic hydrocarbons were present in Shatt AL-Hilla among which 16 polycyclic aromatic hydrocarbons on the US-environmental protection agency priority pollutants list. The contamination with polycyclic aromatic hydrocarbons were variant from site to site in both (values of concentrations and existence of contaminants compounds) that may be return to the type pollutant sources, which it also was differ from site to site. Bulk deposition and domestic effluent are suggested as the main sources of polycyclic aromatic hydrocarbons pollutants in surface waters.